How Oyster Reefs Can Affect Finfish Recruitment - Gabrielle Love; Anna Braswell; Angela B. Collins; Edward Camp (EDIS)
Recruitment is a very important life stage for fish which has direct impacts on size of the whole fish population. During this phase, the mortality juvenile fish experience is affected by their density because of competition for the available resources. How much fish density affects mortality in recruitment is itself affected by many factors, but one of the most important is the structural habitat available to juvenile fish. Structurally complex habitats like oyster reefs are thought to have a particularly strong influence on the recruitment process of certain species. Here we describe the ways that habitat can alter recruitment success. We focus on how oyster reefs affect recruitment of fish in Florida and the particular issues related to management of this important habitat.